Vegetation structure mediates a shift in predator avoidance behavior in a range-edge population. (2nd June 2018) - Johnston, Cora A; Smith, Rachel S
Abstract : Behavioral changes can be the difference between life and death for organisms living in novel habitat along their species' range edge. Tree-climbing crabs, which occur in grassy marshes beyond the range of their primary mangrove habitat, swap predator avoidance behaviors to match escape opportunities provided by each habitat's distinct vegetation growth forms. Such behavioral matching can occur faster than adaption and may enhance the persistence of range-edge populations as climate rearranges species and their habitats. Abstract: Where organisms encounter novel conditions during range expansion, behavioral changes suited to the new habitat can enhance survival. Behavioral changes that mitigate predation risk are particularly important for the persistence of range-edge populations, especially where plastic responses outpace genetic adaptation. We use a climate-driven spatial mismatch between the arboreal mangrove tree crab ( Aratus pisonii ) and its primary mangrove habitat to evaluate differences in predator avoidance behavior between populations in range-center mangroves and adjacent range-edge salt marshes. We expected that differences in vegetation stature and diameter mediate changes in Aratus behavior. We combined crab and vegetation surveys with tethering experiments and in situ behavioral trials to determine habitat-specific predation risk and predator avoidance via evasion and autotomy. Tethering trials revealed that predation risk was always greater from aquatic sources than terrestrial sources and that aquatic risk was enhanced in marsh habitat. Vegetation structural form constrained Aratus predator avoidance during in situ behavioral assays: in mangroves, Aratus escaped upward into the canopy, but short-statured marsh grass restricted evasion to downward movement towards the higher risk aquatic environment. Given this restricted evasion route, Aratus in salt marshes were less likely to evade and showed more evidence of secondary escape via leg dropping. Shifting predator avoidance behavior away from a fleeing escape strategy may ameliorate the fitness costs of reduced escape opportunities for Aratus in novel marsh habitat along the range edge. Similar changes in behavior to match local habitat conditions could be integral to the persistence of many range-edge populations that encounter novel habitats.